Strategi Branding Akun Instagram Dari Aplikasi Bawapulang: Pendekatan Strategis Dalam Pemasaran Digital - Gadis Cantik Bunga Tunjungwangi; Restu Ismoyo Aji (Pusat Riset dan Inovasi Nasional, 2023)
Branding strategy is an important approach used by every company to promote their brand, products, and services. The branding strategy employed by the Instagram account @bawapulang involves diverse content, such as promotional content aimed at expanding market reach. Additionally, content that includes entertainment like memes and games will foster a closer relationship between BawaPulang and its audience, further broadening its market outreach. Informative content featuring tips and tricks about business will also impact the expansion of market reach, as it won't just engage the account followers but also individuals need these tips and tricks. This journal will highlight the importance of consistent diverse content in building a brand.